Oxygen isotope studies of phosphite oxidation: Purification and analysis of reactants and products by high‐temperature conversion elemental analyzer/isotope ratio mass spectrometry. (27th September 2015) - Chang, Sae Jung; Blake, Ruth E.
<x xml:space="preserve">Abstract</x> Rationale Increased attention has been recently focused on the origin and reactions of reduced‐P oxyanions such as phosphite [PO3(III)] in terrestrial and biological systems. We present new methods for studying O‐isotopic reactions between PO3(III) and other oxygen sources during oxidation of PO3(III) to PO4(V). Methods Na2(HPO3)·5H2O, used as a PO3(III) source, contains structural water due to its hygroscopic nature; thus, we developed a method for determining the δ18O value of PO3(III) after the removal of structural water. Next, we tested two techniques for purifying PO4(V) from aqueous PO3(III)/PO4(V) mixtures: (1) precipitation of PO4(V) as ammonium phosphomolybdate (APM); and (2) precipitation of PO4(V) as magnesium ammonium phosphate (MAP). The O‐isotope compositions, 18O:16O (δ18O values), of Na2(HPO3) and Ag3PO4 were analyzed by TC/EA/IRMS. Results Structural water was removed from Na2(HPO3)·5H2O after drying at 100 °C under vacuum and the δ18O value of PO3(III) was obtained. The δ18O values of PO4(V), which was extracted from 18O‐labeled PO3(III)/PO4(V) mixtures by APM and MAP precipitations, were not altered by the precipitation process. This result confirms that PO3(III) is not converted into PO4(V) by oxidation or hydrolysis under either strong acidic/oxidizing (APM) or alkaline (MAP) conditions for up to a 24‐h period. Conclusions We conclude that both APM and MAP precipitation are reliable and effective methods for the separation and purification of PO4(V) from aqueous PO3(III)/PO4(V) mixtures. The methods described here will permit the study of the isotopic evolution of various pathways of geochemical as well as biological PO3(III) oxidation. Copyright © 2015 John Wiley & Sons, Ltd.